Pengembangan dan Perancangan Perjalanan Pelanggan dan Sistem Informasi Penjualan pada Coffee Shop Frekuensi Kopi - Iwan Darmawansyah; Sismiati Sismiati (Neolectura, 2021)
The consumer journey is one of the marketing techniques that must be considered by business owners. From the customer journey, business owners can develop 2 outcomes, including the conversion of marketing activities to sales, and also advocates from advocates who have purchased or even only seen reviews of the consumer journeys they have experienced. The application of computer technology as a tool that is absolutely used as the main support in business competition and the support of good human resources. To support this achievement, it is necessary to have an information system that can assist in facilitating all processes required by the company. The problem with Coffee Frequency is how to design a sales information system that is appropriate and needed by Kopi Frequency. With the aim of research to create an application that can process sales data on Frequency Kopi computerized and provide a customer journey strategy for the owner of the Coffee Frequency Coffee Shop. The data collection method used by the author is qualitative with a case study approach by applying Research and development (R&D). This study resulted in a sales information system design to process data, in the form of goods data, supplier data, incoming and outgoing stock data, so that the sales process can run more precisely and quickly and provide a pleasant customer journey.